SOSOK VLADIMIR PUTIN DALAM PEMBERITAAN KONFLIK RUSIA-UKRAINA OLEH DETIK.COM - Noven Harjadi, Christian; Lukmantoro, Triyono; Hasfi, Nurul (Interaksi Online, 2024)
This research is based on the author's interest in the framing of Russian President Vladimir Putin, who is frequently reported by Detik.com as an influential figure in the Russia-Ukraine conflict. In these reports, the image of Vladimir Putin receives significant attention from journalists, ranging from his political career trajectory, the motives behind his command to deploy Russian military operations in Ukraine, to Putin's responses to foreign policy decisions impacting Russia's status on the international stage. This framing has the potential to create bias where the Indonesian online community may develop greater sympathy for Russia and even admire Vladimir Putin. The data collection tool used in this research consists of 25 relevant news articles from Detik.com concerning the figure of Russian President Vladimir Putin in the Russia-Ukraine conflict during the 24-hour period following Russia's attack on Ukrainian territory on February 24, 2022. This research employs Robert N. Entman's framing method with the aim of defining problems, identifying causes, conducting moral evaluations, and offering solutions to the issues in reporting on the Russia-Ukraine conflict related to the figure of President Putin. This research concludes that there are five framings of Vladimir Putin carried out by Detik.com, namely: (1) Vladimir Putin holds ideals that conflict with the Ukrainian government, the United States, and their allies as opposition; (2) Vladimir Putin wants to protect the lives of Ukrainian soldiers and maintain Ukraine as a neutral state free from Western influence; (3) Vladimir Putin is portrayed as an aggressor responsible for military operations and causing a humanitarian crisis in Ukraine; (4) Vladimir Putin is depicted as an ally of Belarus, successfully garnering support for launching military operations in Ukraine; and (5) Vladimir Putin is portrayed as a decisive Russian leader with an authoritarian and charismatic side.